PERBANDINGAN GAYA GESER DASAR SEISMIK DI PULAU JAWA MENGGUNAKAN METODE RESPON SPEKTRUM - besty afriandini; Cremona Ayu Novita Sari; Arif Kurniawan Suksmono (Racic : Rab Construction Research, 2022)
In 2019 the National Standards Agency of Indonesia officially set the earthquake-resistant building planning standard, SNI 1726-2019, revising the previous standard, SNI 1726-2012. Changes in several parameters of earthquake resistance will affect changes in the spectrum response as an earthquake load. This study aims to compare the value of the seismic base shear using the response spectrum method with the application of SNI 1726-2012 and SNI 1726-2019 in 6 cities on the Java Island, namely Banten, Jakarta, Bandung, Semarang, Yogyakarta, and Surabaya. Structural modeling using SAP 2000 software and the analysis method used is the response spectrum method. The x-direction seismic base shear based on SNI 1726-2019 at 6 locations is 2666,184 ; 2537,047 ; 3225,123 ; 2829,838 ; 3202,125 and 2333,256 kN. The y-direction seismic base shear on SNI 1726-2019 produces 2783,057 ; 2648,228 ; 3366,417 ; 2953,858 ; 3342.421 and 2435.54 kN. The seismic base shear in the x-direction and the y-direction in 6 cities reviewed based on SNI 1726-2019 shows a bigger than SNI 1726-2012. The largest seismic base shear based on SNI 1726-2012 and SNI 1726-2019 in the X-direction and Y-direction are in the city of Bandung, concur to the results of the Response Spectrum calculations of the two regulations, which show the largest value is in the city of Bandung.